Moldova Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank Group (World Bank, Washington, DC, 2016)
Financial reporting and auditing practices in Moldova's corporate sector are currently in a period of transition from providing for tax calculation and statistical needs to convergence with International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA). This report draws upon recent international experience in developed economies and EU accession countries as well as expected amendments to EU Directives. The National Accounting Standards (NAS) were developed on the basis of International Accounting Standards (IAS) from 1996 to 1998 for the most part, but they are substantially incomplete and out of date vis-à-vis IFRS (which incorporate IAS). Accordingly, the standard-setting process should be streamlined so as to allow the prompt adoption of the numerous existing IASs not yet reflected in the NAS. The National Standards of Auditing were developed recently and mirror ISA. The existing Accounting Law and certain aspects of the Joint Stock Companies Law are unduly onerous and restrictive in that they demand bookkeeping and other administrative procedures not normally required in market economy systems. These conflict with mandated accounting standards, confuse the preparers of financial statements and are detrimental to the quality of the financial information. A new Accounting Law should be passed with simplified requirements and incorporating key elements of the NAS and relevant EU Directives on that matter.